Quality assurance for environmental analysis method evaluation within the Measurements and Testing Programme (BCR) - Quevauviller, Ph.; Maier, E. A.; Griepink. B. (Amsterdam ; New York : Elsevier, 1995)
Quality assurance (QA) for environmental analysis is a growing feature of the nineties as is illustrated by the number of QA guidelines and systems which are being implemented nowadays. There is, however, often a huge gap between the implementation and respect of QA guidelines and the technical approach undertaken to improve and validate new analytical methods. This is particularly true for complex determinations involving multi-step methodologies such as those used in speciation and organic analyses. Quality assurance may also be considered from the technical point of view, which is the focus of this book. The techniques used in different analytical fields (inorganic, speciation and organic analysis) are critically reviewed (i.e. discussion of advantages and limitations) and existing tools for evaluating their performance are described (e.g. interlaboratory studies, use of certified reference materials). Particular reference is made to the activities of the Measurements and Testing Programme (BCR) of the European Commission towards the improvement of quality control of environmental analysis. The book has been written by experienced practitioners. By its nature, it serves as a practical reference for postgraduate students and environmental chemists who need a wide overview of the techniques used in environmental analysis and existing ways of evaluating the performance of relevant analytical methods. The critical discussions of the methods described, as well as the development of quality assurance aspects, makes it unique.
Quality assurance for environmental analysis / Ph. Quevauviller, E.A. Maier and B. Griepink -- Isotope dilution analysis and ICP-MS : an analyst's dream? / M.J. Campbell -- Detection of sources of error in the determination of Cr in environmental matrices by FAAS and ETAAS / A. Sahuquillo, R. Rubio and G. Rauret -- Analysis of environmental and biological samples by atomic spectroscopic methods / M. Hoenig and M.F. Guns -- Validation of neutron activation analysis techniques / K. Heydorn -- Flow-through (bio)chemical sensors in environmental analysis / M.D. Luque de Castro and M. Valcarcel -- Fiber optical sensors applied to field measurements / C. Camara, C. Perez-Conde, M.C. Moreno-Bondi and C. Rivas -- Chromium speciation in environmental and biological samples / K. Vercoutere and R. Cornelis -- Determination of aluminium species in natural waters / B. Fairman and A. Sanz-Medel -- Selenium speciation analyses in water and sediment matrices / C. Camara, M.G. Cobo, M.A. Palacios, R. Mu{tilde}noz and O.F.X. Donard -- Antimony speciation in water / M.B. de la Calle-Guntinas, Y. Madrid and C. Camara -- Arsenic speciation in environmental matrices / B. Amran, F. Lagarde, M.J.E. Leroy, A. Lamotte, C. Demesmay, M. Olle, M. Albert, G. Rauret and J.F. Lopez-Sanchez -- Mercury speciation in biological matrices / I. Drabk and A. Iverfeldt -- Speciation analysis of organolead compounds. Status and future prospects / R. {Lstrok}obi{acute}nski, W.M.R. Dirkx, J. Szpunar-{Lstrok}obi{acute}nska and F.C. Adams -- Speciation analysis of organotin by GC-AAS and GC-AES after extraction and derivatization / W.M.R. Dirkx, R. {Lstrok}ob{acute}nski and F.C. Adams -- High performance liquid chromatography, isotope dilution : inductively coupled plasma, mass spectrometry for lead and tin speciation in environmental samples / S.J. Hill, A. Brown, C. Rivas, S. Sparkes and L. Ebdon -- Speciation of organotin compounds in environmental samples by GC-MS / R. Morabito, S. Chiavarini and C Cremisini -- Development of supercritical fluid extraction procedures for the determination of organotin compounds in sediment / J.M. Bayona -- Hydride generation for speciation analyses using CG/AAS / R. Ritsema, F.M. Martin and Ph. Quevauviller -- Single and sequential extraction schemes for trace metal speciation in soil and sediment / A.M. Ure, C.M. Davidson and R.P. Thomas -- Methods for the determination of chlorinated biphenyls in air / M. Morosini and K. Ballschmiter -- Sample handling and determination of carbamate pesticides and their transformation products in various matrices / M. Honing, D. Barcelo, B.L.M. van Baar and U.A.Th. Brinkman -- Method development for the determination of polycyclic aromatic hydrocarbons (PAHs) in environmental matrices / J. Jacob -- Method validation for the determination of dioxins / T. Rymen.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Chemical laboratories -- Quality control; Chemistry, Analytic -- Quality control; Chemistry, Analytic -- Technique; Electronic books